ظاهرة الأسر العلمية في أقاليم المشرق الاسلامي في العصر الوسيط من خلال نماذج - شارف, خالد (جامعة الوادي - University of Eloued, 2023)
تعتبر الأسر العلمية واحدة من أهم العوامل التي ساهمت في التطور العلمي والرقي الحضاري الذي شهده المشرق الإسلامي، لذلك جاءت هذه الدراسة لتسلط الضوء على ذلك وتؤكد أنه ظاهرة عامة شملت جميع ربوع العالم الاسلامي، وبالأخص منه أقاليم المشرق الاسلامي بدءا بالعراق، مرورا ببلاد الشام، ثم بلاد فارس، فبلاد ما وراء النهر، حيث توقفنا عند الظاهرة ومفهومها وظروف بروزها، ثم ذكر نماذج عنها من تلك الأقاليم لنؤكد على أن الأمر كان ظاهرة اسلامية في العصر الوسيط. The Scientific families are considered one of the most important factors that contributed to the scientific development and civilizational advancement witnessed by the Islamic East. Therefore, this study came to shed light on that and confirm that it is a general phenomenon that covered all parts of the Islamic world, especially the regions of the Islamic Mashreq, starting with Iraq, passing through the Levant, then Persia, beyond the river, where we stopped at the phenomenon, its concept and the circumstances of its emergence, then mentioned examples of it from those regions to confirm that the matter was an Islamic phenomenon in the medieval era.
مقال
Keywords: البيوتات العلمية ; المشرق الاسلامي ; بغداد ; فارس ; الشام ; ما وراء النهر; scientific families; the Islamic Orient; Baghdad; the Levant; Persia; Transoxiane